Features during epidural anesthesia in gynecological patients with different tolerance to transient hypoxia and hypercapnia - M. V. Golovataya; I. F. Dynko (Кубанский научный медицинский вестник, 2015)
The specific features of epidural anesthesia and an early postoperative period were studied in gynecological patients with different tolerance to transient hypoxia and hypercapnia. The relationship of low tolerance to transient hypoxia and hypercapnia and instable hemodynamics as vasoplegia, which was a risk factor of perioperative complications, including postoperative nausea and vomiting, was proven.